Autonomy Orientation and Innovative Work Behavior <subtitle>Τhe Mediating Role of Creativity and Prosocial Motivation</subtitle> - Konstantinos Papachristopoulos; Alexios Arvanitis (European Journal of Psychology Open, 2024)
Abstract: Introduction: Innovative work behavior (IWB) has a built-in, definitional association with elements of creativity and the provision of benefits to others within the work context. Because of the properties of IWB and the nature of autonomy, as conceptualized by self-determination theory, we hypothesized that autonomy orientation would be positively associated with IWB through the mediating role of both creativity and prosocial motivation. Aim: The study examines the relationship of dispositional autonomy with IWB and offers evidence for potential explanatory mechanisms of how autonomous forms of motivation are associated with IWB. Method: We conducted a cross-sectional study in Greece and Canada, wherein employees (N = 528) completed assessments of causality orientations at work, prosocial motivation, creativity and IWB. Results: Autonomy orientation, creativity, and prosocial motivation were positively associated with IWB, whereas controlled and impersonal orientations were negatively associated with IWB. Mediation analyses showed that creativity and prosocial motivation mediated the relationship between causality orientations and innovative work behavior. Discussion and conclusion: Our findings extend prior research on the role of autonomy and prosocial motivation on innovative and creative behavior at work.